PENGUATAN WILAYAH PERBATASAN: STUDI KASUS PULAU SEBATIK KABUPATEN NUNUKAN PROVINSI KALIMANTAN TIMUR - Wicaksono, Baskoro (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
This study describes the border management policy conducted by the central government, provinceof East Kalimantan and Nunukan. Policies such as the establishment of regulatory, institutionalstrengthening, programs and infrastructure development. The policy is getting good responsefrom the elite and the masses. On the other hand policy makers have expectations of localcommunities border synergism Sebatik Island in order to build and develop the border areas so asto break the chain of dependence on Malaysia. The research was conducted in Sebatik Island,East Kalimantan province Nunukan with the formulation of the problem (a) what policies areoriented to maintain borders, (b) How is the public response to government policy, (c) What areyour expectations of policy makers in local communities to regional border. This study usedqualitative methods to phenomenological research strategy. Techniques of data collection in thisstudy using two ways, namely in-depth interviews and secondary data view Results indicate thatthe existing policy of both the central and provincial to district borders do not solve the problembecause it is made on the island of Sebatik with other border regions. The policy does not includelocal knowledge, where it is desperately needed by the people Sebatik. In addition to policies onprograms and infrastructure development of the center, the district adopted a policy of inactionagainst the illegal cross-border trade, which on the one hand against the rules but if enforced thenpeople can not perform economic activities that impact well-being. Policies like this gets a positiveresponse from the public. Expectations for the future border policy is to load local content orlocal knowledge.Keyword: border policy, local knowledge, dependent relationship